Development of long-term practical solutions to the universal problem of biofilm contamination of dental unit waterlines - O'Donnell, Mary J. (Trinity College (Dublin, Ireland). School of Dental Science, 2009)
Microbial contamination of dental chair unit (DCU) output water by biofilm growth in dental unit waterlines (DUWLs) is a universal problem and a potentially significant source of cross-infection. At the outset of this project the emphasis on DUWL biofilm in the literature focused on describing the problem and attempts at its control using a range of DUWL treatment agents. However, no long-term studies on the efficacy of DUWL disinfection using a large number of DCUs have been reported. Furthermore, until recently, DCU manufacturers have been slow in developing DCU design changes to facilitate DUWL biofilm control.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin